Kid vs. squid - Van Eekhout, Greg (Bloomsbury Children's Books : Distributed to the trade by Macmillan, 2010)
Spending the summer after sixth grade at his great-uncle's oceanside museum, Thatcher and local girl Trudy team up to help Shoal, one of the people of Atlantis cursed by a witch whose head still survives, and who has an army of monstrous creatures helping her.